2020
DOI: 10.3390/rs12244184
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Climate Variability and Drought on Surface Water Resources in Sub-Saharan Africa Using Remote Sensing: A Review

Abstract: Climate variability and recurrent droughts have caused remarkable strain on water resources in most regions across the globe, with the arid and semi-arid areas being the hardest hit. The impacts have been notable on surface water resources, which are already under threat from massive abstractions due to increased demand, as well as poor conservation and unsustainable land management practices. Drought and climate variability, as well as their associated impacts on water resources, have gained increased attenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(53 citation statements)
references
References 124 publications
1
30
0
1
Order By: Relevance
“…Drought is a component of the natural variability in climate on the African continent, with quite high intensities at monthly, yearly, decadal, or century timescales. Some studies have reported on how climate change, aerosol emissions, land use practices, and subsequent land-atmosphere interactions, have led to mechanisms inducing droughts (Masih et al, 2014;Bhaga et al, 2020). Moreover, El Niño-Southern Oscillation (ENSO) and sea surface temperatures (SSTs) are considered as key factors influencing drought across SSA (Masih et al, 2014).…”
Section: Impacts Of Climate Change On Water Land and Food Resources In Ssa Climate Change And Water Resources In Ssamentioning
confidence: 99%
See 2 more Smart Citations
“…Drought is a component of the natural variability in climate on the African continent, with quite high intensities at monthly, yearly, decadal, or century timescales. Some studies have reported on how climate change, aerosol emissions, land use practices, and subsequent land-atmosphere interactions, have led to mechanisms inducing droughts (Masih et al, 2014;Bhaga et al, 2020). Moreover, El Niño-Southern Oscillation (ENSO) and sea surface temperatures (SSTs) are considered as key factors influencing drought across SSA (Masih et al, 2014).…”
Section: Impacts Of Climate Change On Water Land and Food Resources In Ssa Climate Change And Water Resources In Ssamentioning
confidence: 99%
“…Moreover, the Horn of Africa which includes Djibouti, Eritrea, Ethiopia, and Somalia, have experienced extreme droughts from 2010 to 2011, caused issues of food insecurity that affected about 20 million people, leading to a significant loss of lives. Drought in Somalia, Kenya, and Ethiopia, contributed to socio-economic instabilities, where Somalia alone recorded 250,000 deaths during the same period (Bhaga et al, 2020). There is medium confidence that droughts will intensify in East and Southern Africa during the twenty-first twenty-first in some seasons, because of reduced precipitation and/or increased evapotranspiration (Niang et al, 2014).…”
Section: Impacts Of Climate Change On Water Land and Food Resources In Ssa Climate Change And Water Resources In Ssamentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have worked on LST determination by remote sensing for many purposes (Li et al, 2013;Qin Karnieli, 1999;Schmugge et al, 2002;Zhou et al, 2012). For example: evapotranspiration modelling (Courault et al, 2005), soil moisture estimation (Sajjad et al, 2010), climatic, hydrological, ecological and biogeochemical studies (Bhaga et al, 2020) are based on the knowledge of the land surface temperature. Therefore, it is very important to have access to reliable LST estimation at large spatial and temporal scales.…”
Section: Introductionmentioning
confidence: 99%
“…Of these extreme events, drought is one of the extreme weather conditions that affects more people than any other form of natural disaster (Wilhite, 2000). The occurrence of drought in recent decades in West Africa highlights the importance of this phenomenon (Bhaga et al, 2020;Faye et al, 2017). Moreover, climate projections have shown that West Africa will experience a significant increase in temperature, with high variability in rainfall (Kouakou et al, 2014;Kouamé et al, 2014;Ly et al, 2013;Yapo et al, 2020).…”
Section: Introductionmentioning
confidence: 99%